Nitrate promoted mild and versatile Pd-catalysed C(sp2)–H oxidation with carboxylic acids. Issue 34 (24th August 2020) - Xiong, Xue; Mao, Yang-Jie; Hao, Hong-Yan; He, Yu-Ting; Xu, Zhen-Yuan; Luo, Gen; Lou, Shao-Jie; Xu, Dan-Qian
Abstract : A nitrate-promoted Pd-catalysed cross-dehydrogenative C(sp 2 )–H oxidation of oximes or azobenzenes with diverse aromatic and aliphatic acids was developed, allowing the versatile formation of O -aryl esters under mild reaction conditions. Abstract : A nitrate-promoted Pd-catalysed mild cross-dehydrogenative C(sp 2 )–H bond oxidation of oximes or azobenzenes with diverse carboxylic acids has been developed. In contrast to the previous catalytic systems, this protocol features mild conditions (close to room temperature for most cases) and a broad substrate scope (up to 64 examples), thus constituting a versatile method to directly prepare diverse O -aryl esters. Moreover, the superiority of the nitrate additive in this mild transformation was further determined by experimental and computational evidence.